The Effect of Negative Learning-related Emotions on Higher Education Faculty's Online Professional Development - Qian Wang; Haibo Gu; Xiaochen Lin (Adult Education Research Conference, 2023)
This research examined how faculty's negative learning-related emotions were associated with their technology acceptance and learning engagement in online professional development.
Keywords: Negative academic emotions; technology acceptance; online learning engagement; HE faculty' s online professional development